Self-assisted wound healing using piezoelectric and triboelectric nanogenerators. Issue 1 (31st December 2022) - Kao, Fu-Cheng; Ho, Hsin-Hsuan; Chiu, Ping-Yeh; Hsieh, Ming-Kai; Liao, Jen‐Chung; Lai, Po-Liang; Huang, Yu-Fen; Dong, Min-Yan; Tsai, Tsung-Ting; Lin, Zong-Hong
ABSTRACT: The complex process of wound healing depends on the coordinated interaction between various immunological and biological systems, which can be aided by technology. This present review provides a broad overview of the medical applications of piezoelectric and triboelectric nanogenerators, focusing on their role in the development of wound healing technology. Based on the finding that the damaged epithelial layer of the wound generates an endogenous bioelectric field to regulate the wound healing process, development of technological device for providing an exogenous electric field has therefore been paid attention. Authors of this review focus on the design and application of piezoelectric and triboelectric materials to manufacture self-powered nanogenerators, and conclude with an outlook on the current challenges and future potential in meeting medical needs and commercialization. Grpahical Abstract: uf0001